Global, Regional, and National Consumption of Sugar-Sweetened Beverages, Fruit Juices, and Milk: A Systematic Assessment of Beverage Intake in 187 Countries - Singh,GM; Micha,R; Khatibzadeh,S; Shi,P; Lim,S; Andrews,KG; Engell,RE; Ezzati,M; Mozaffarian,D (PLOS One, 2015)
BackgroundSugar-sweetened beverages (SSBs), fruit juice, and milk are components of diet of major public health interest. To-date, assessment of their global distributions and health impacts has been limited by insufficient comparable and reliable data by country, age, and sex.ObjectiveTo quantify global, regional, and national levels of SSB, fruit juice, and milk intake by age and sex in adults over age 20 in 2010.MethodsWe identified, obtained, and assessed data on intakes of these beverages in adults, by age and sex, from 193 nationally- or subnationally-representative diet surveys worldwide, representing over half the world’s population. We also extracted data relevant to milk, fruit juice, and SSB availability for 187 countries from annual food balance information collected by the United Nations Food and Agriculture Organization. We developed a hierarchical Bayesian model to account for measurement incomparability, study representativeness, and sampling and modeling uncertainty, and to combine and harmonize nationally representative dietary survey data and food availability data.ResultsIn 2010, global average intakes were 0.58 (95%UI: 0.37, 0.89) 8 oz servings/day for SSBs, 0.16 (0.10, 0.26) for fruit juice, and 0.57 (0.39, 0.83) for milk. There was significant heterogeneity in consumption of each beverage by region and age. Intakes of SSB were highest in the Caribbean (1.9 servings/day; 1.2, 3.0); fruit juice consumption was highest in Australia and New Zealand (0.66; 0.35, 1.13); and milk intake was highest in Central Latin America and parts of Europe (1.06; 0.68, 1.59). Intakes of all three beverages were lowest in East Asia and Oceania. Globally and within regions, SSB consumption was highest in younger adults; fruit juice consumption showed little relation with age; and milk intakes were highest in older adults.ConclusionsOur analysis highlights the enormous spectrum of beverage intakes worldwide, by country, age, and sex. These data are valuable for